A Coordinated Operation Control Strategy of Multiple Phase Shifting Transformers Based on the Interaction Sensitivity - Huarui Li; Ningyu Zhang; Yuqiao Jia; Xinyao Zhu (IEEE Access)
With the continuous expansion of power system scales and the increasing integration of renewable energies, the issues such as the line overload have become prominent, which result in the growing demand for power flow control in the power system. As a low-cost and effective power flow regulation device, Phase Shifting Transformers (PSTs) are gradually being deployed at a larger scale. However, the control characteristics and application scenarios of different types of PSTs are different. In the case of independent operation without considering multiple PSTs’ interactive effects, their control performances may be suboptimal or even counterproductive. In order to achieve coordinated optimization of multiple PSTs, this paper proposes a coordination control strategy based on the interaction sensitivity. By quantifying the interactions between PSTs, a multi-objective coordination control algorithm is designed to optimize the system’s power flow control performance, voltage stability, and loss rate. The simulation results based on the IEEE 57-bus system verify the effectiveness of the proposed strategy. Compared to independent control strategies, the coordination control strategy reduces the maximum line loading rate by 3.79%, the node voltage deviation index by 0.02%, and the system loss rate by 0.01%.